“Off-label” drugs: legal problems and socio-economic aspects of application practice - S. V. Russkikh; E. A. Tarasenko; L. I. Moskvicheva; S. A. Orlov; A. A. Tryakin; A. V. Vorobeva; O. A. Beneslavskaya; V. I. Makarova; E. A. Putilina; S. A. Utkin (Фармация и фармакология (Пятигорск))
The aim of the work was to analyze Russian and foreign experience in the regulation and application practice of “off-label” drugs in order to develop recommendations on the optimization of their application in clinical practice.Material and methods. The analysis of scientific articles and legal documents of the Russian Federation and foreign countries published from 2011 to 2022 on the websites Consultant Plus, FDA, EMA, NCBI, e-library, as well as a qualitative sociological study conducted in May-August 2022 ‒ 11 in-depth interviews with experts in the field of the healthcare system of the Russian Federation.Results. The social and economic aspects have been considered and the list of legal problems in the application practice of “off-label” drugs has been disclosed. A state analysis of the regulatory and legal framework on the drugs application practice by healthcare professionals in the absence of registered indications for “off-label” drugs use has been presented. The use of an unregistered medicinal product in the territory of the Russian Federation in everyday medical practice has been considered. The analysis of the Russian and foreign experience in regulating the use of drugs in the absence of their registration in the country, as well as the absence of registration of some indications for their prescription in the instructions for the medical use of such drugs has been also carried out. The authors have formulated the key problems of the use of “off-label” drugs in clinical practice. Based on the results of the in-depth interviews, the recommendations of the expert community on the ways to optimize the use of “off-label” drugs have been identified and concretized.Conclusion. The results of this study made it possible to formulate recommendations for expanding the ability of specialists to prescribe “off-label” drugs treatment while maintaining a proper degree of the state control over this process: a legislative consolidation of the regional health authorities’ obligations and responsibilities on the drug provision; creating an open and transparent system for the “off-label” drugs use by patients and their legal representatives, the mandatory full information of the patient about the fact of using the “off-label” drug, as well as the risk and nature of the development of possible adverse reactions. When prescribing these drugs, the patient safety should be the top priority.